TUBERCULOSIS PNEUMONIA, A TYPICAL PRESENTATION OF PULMONARY TB. - Ghaed; a J. Al-Ghizawi (Basrah Journal of Veterinary Research)
This study was carried out to see the pattern of pneumonic disease in Basrah general hospital in the two groups of patients, inpatients out patients and to see the extent of tuberculosis presented as pneumonia, not as atypical case of clinical and X-ray findings in the apices of lungs. This is prospective study for patients with typical history, signs investigation chest x-ray of pneumonia, lobar and bronchopneumonia from the period of (April 2006) to (October 2008) were included in this study, they are attending the out patient department or are admitted in the wards of the Basrah general hospital. From a total of 374 cases of pneumonia, 26 cases of TB pneumonia diagnosed. There findings did not suggest TB to start. There age range from one to 72 years, the most common age group affected was 20-40 year for both sexes, while at age group 50-70 males affected more, bronchopneumonia was comment type of pneumonia in this group recorded in 13 patients, or bronchitis in 6 patients. ESR was less than 50 mm/hr in 12 patients so it is unreliable in 50% of cases. This study show that pulmonary TB is increasing (5.36%) and it could present in pneumonia like picture not involving the typical sites (apices) even in those who are not diabetic or immune compromised.